Persepsi Petani dalam Pengelolaan Kawasan Penyangga Tahura BJ. Habibie di Desa Bihe, Kecamatan Asparaga : Tantangan dan Strategi Keberlanjutan - Eka Reza Saputra Widodo; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The buffer zone of BJ. Habibie Grand Forest Park (Tahura) in Bihe Village, Asparaga District, plays a strategic role in balancing environmental conservation and community agricultural activities. However, the widespread practice of monoculture corn farming and land clearing through burning threatens ecosystem sustainability and accelerates environmental degradation. This study aims to analyze farmers’ perceptions of buffer zone management and to identify the challenges and potential for transitioning to sustainable agricultural systems. A descriptive qualitative and quantitative approach was used through field observations, in-depth interviews, questionnaires, and document analysis. The findings indicate that most farmers possess basic awareness of the importance of conservation areas, but there are notable knowledge gaps regarding regulations and environmentally friendly practices. Although some farmers acknowledge the negative impacts of land burning and monoculture, economic limitations, inherited customs, and lack of technological support remain significant obstacles. Nevertheless, respondents expressed a high willingness to change their farming practices if provided with training and incentives. This study recommends a participatory strategy involving government bodies, conservation institutions, and academics to build farmers’ capacity and promote the adoption of sustainable agricultural technologies. A collaborative approach that considers the socio-economic realities of local communities is essential to ensure the long-term sustainability of the BJ. Habibie buffer zone without compromising farmers’ welfare.